PENGARUH LATIHAN HURDLE DRILL TERHADAP FREKUENSI TENDANGAN PADA SISWA PENCAK SILAT PSHT RAYON SIKUR - Wijaya Kusuma, Lalu Sapta; Aminullah, Aminullah (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
Abstract: The ability of a fighter to perform a kick motion with a good frequency is one of the factors in conducting this research. The main objective of this study is to determine the extent to which hurdle training affects kick frequency, especially in the PSHT Rayon sikur fighter in 2020. This research is in the form of an experiment using a pretest treatment, and posttest to determine the difference in numbers before and after being given treatment. Subjects in this study amounted to 10 people. The design used in this study was one group pretest and postest design. The data analysis technique used was a similar sample t-test with 5% degrees of freedom in the N-1 number. The results showed that from statistical calculations, the t-count was 10.38, and the t-table was 1.883, or in other words 10.38> 1.883. So it can be concluded that the results of this study are that there is an effect of hurdle training on the frequency of kicks in the PSHT Rayon Sikur fighter